Quality in computorized tomography: from image acquisition to dose, concepts, myths and definitions - Abrantes, António (2022)
With this review article, we intend to demonstrate the importance of Computerized Tomography (CT) in healthcare quality and safety. The concept of safety in CT is wider than for general healthcare. Safe healthcare provided using CT must include diagnostic image quality and reliability, as this is the only way to ensure diagnostic accuracy. The images must be acquired with the most adequate protocols available and with the lowest achievable radiation dose. In this article we will focus primarily on the concepts of dose, since this variable strongly affects the image quality and the consequent diagnostic accuracy. In methodological terms, 73 papers and 6 catalogues issued by the manufacturers of CT equipment, that included the keywords low dose, ultra-low dose and dose reduction were analysed. After review of these articles we found that about 82% are chest exams, namely the lungs. The remaining were subdivided mainly by studies of the sinuses, heart and bone segments. After this review we selected the only 10 articles that present the keywords and simultaneously quantify the dose reduction. Given the lack of precision associated with these terms, introduced mainly by commercial catalogues of different equipment brands, we intend to demonstrate that the concepts low dose and ultra-low dose are wrapped in unclear marketing strategies, without a strict and unambiguous definition of what is the effective dose. We propose that these concepts should be clearly defined and a precise indication of the effective dose reduction value should be compared to the default value (standard diagnostic dose) by exam region. Therefore, it is demonstrated that there is no concrete definition of what low dose or ultra-low dose are. These slogans cannot be used until they are not holistically defined, as well as the correspondent dose reduction value.